Could sex-specific subtypes of hand osteoarthritis exist? A retrospective study in women presenting to secondary care - Gulati, Malvika; Brewer, Gretchen; Judge, Andrew; Kennedy, Donna; Vincent, Tonia L.; Watt, Fiona E. (Frontiers in Pain Research, 2024)
Introduction Hand osteoarthritis is more common in women, and its risk increases around the time of the menopause. We set out to describe the timing between menopause and the onset of symptomatic hand osteoarthritis (OA), and associations with the use of hormone replacement therapy (HRT) or its discontinuation, describing any identifiable subgroups of women. Methods Retrospective healthcare-records study of sequential women referred to a specialist hand OA clinic, 2007–2015. Confirmation of hand OA diagnosis was by clinican, by accepted criteria. Demographics and clinical variables were from healthcare-records, recorded by standardised proforma. Outcomes of interest were reported age of onset of hand symptoms, reported age at final menstrual period (FMP), time from FMP to reported onset of hand symptoms and time from cessation of HRT to reported onset of hand symptoms. Exposure categories for systemic HRT use were never users, current users, previous users. Analysis of Variance compared groups; linear regression analysed associations of exposure with outcome. Results 82/92(89%) of eligible women were post-menopausal, mean age at FMP 49.9 years (SD5.4). In these post-menopausal women, median time from FMP to hand symptom onset was 3 years. 48/82 (59%) developed hand symptoms within the defined peri-menopausal period (FMP ± 4 years), whilst some women developed their symptoms before or after (range −25, 30 years). In women who discontinued HRT prior to symptom onset, the median time from HRT cessation to onset of hand symptoms was 6 months. Past HRT users were older at hand symptom onset than women who had not taken HRT [coeff.4.7 years (0.92, 8.39); P = 0.015]. Conclusions This study adds to evidence associating the menopause/sex hormone deficiency with hand OA symptom onset in a sizeable subgroup of women (but not all). HRT use/cessation appears to influence the timing of onset of hand OA symptoms. It is not possible to interpret from this type of study whether sex hormone deficiency is causative of disease or modulates its symptoms. It is also not possible to judge whether painful hand osteoarthritis in post-menopausal women is a subtype of disease. Further investigation is indicated of sex-specific subtypes and potential for personalised medicine for post-menopausal women with hand osteoarthritis, as a clearly definable high-risk subgroup.